Acquired capability for suicide among Belgian and Australian University students: Psychometric properties of the German capability for suicide questionnaire and a test of the interpersonal theory of suicide - Preece, David; Kiekens, Glenn; Boyes, Mark; Mortier, P.; Nock, M.; Kessler, R.; Bruffaerts, R.; Hasking, Penelope (WILEY, 2021)
Objective: The Interpersonal Theory of Suicide (IPTS) posits fearlessness of death and pain tolerance as two components of suicide capability. The German Capability for Suicide Questionnaire (GCSQ) is the first measure of both these components, but few data are available on its psychometrics. We (a) examined the psychometric properties of the GCSQ and used it to test (b) the latent structure of suicide capability and (c) its associations with suicidal behavior. Method: As part of the WHO World Mental Health International College Student Initiative, Belgian (N = 3715) and Australian (N = 2828) students completed the GCSQ (Dutch or English versions). Results: The factor structure of the GCSQ was well represented by two first-order factors (fearlessness of death, pain tolerance) and a higher-order suicide capability factor. The fearlessness of death scale and pain tolerance scale (minus two reverse-scored items) showed good reliability (α = 0.81– 0.90). Fearlessness of death was associated with suicidal behaviors, but the pain tolerance scale was inversely associated with suicidal behaviors. Conclusions: Consistent with the Interpersonal Theory of Suicide, fearlessness of death and pain tolerance are components of a higher-order suicide capability construct. The GCSQ is a reliable measure of this construct, though its pain tolerance scale requires modification.